2004
DOI: 10.1086/425583
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza A Virus (H7N7) Epidemic in The Netherlands in 2003: Course of the Epidemic and Effectiveness of Control Measures

Abstract: An epidemic of high-pathogenicity avian influenza (HPAI) A virus subtype H7N7 occurred in The Netherlands in 2003 that affected 255 flocks and led to the culling of 30 million birds. To evaluate the effectiveness of the control measures, we quantified between-flock transmission characteristics of the virus in 2 affected areas, using the reproduction ratio Rh. The control measures markedly reduced the transmission of HPAI virus: Rh before detection of the outbreak in the first infected flock was 6.5 (95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
264
3
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(276 citation statements)
references
References 29 publications
4
264
3
5
Order By: Relevance
“…This is in contrast to the experience of the 2003 H7N7 HPAI outbreak in poultry flocks in The Netherlands, in which 255 flocks were infected (Stegeman et al 2004) and to models based on this outbreak (Le Menach et al 2006), which reported a mean of 184 infected farms . Similarly, analysis of data from four HPAI outbreaks (H7N7 in Italy, H7N7 in two areas in The Netherlands and H7N3 in Canada) suggest that even in the face of control measures the reproductive number often remains close to or above 1, highlighting the potential for propagating epidemics (Garske et al 2007).…”
Section: Discussioncontrasting
confidence: 85%
“…This is in contrast to the experience of the 2003 H7N7 HPAI outbreak in poultry flocks in The Netherlands, in which 255 flocks were infected (Stegeman et al 2004) and to models based on this outbreak (Le Menach et al 2006), which reported a mean of 184 infected farms . Similarly, analysis of data from four HPAI outbreaks (H7N7 in Italy, H7N7 in two areas in The Netherlands and H7N3 in Canada) suggest that even in the face of control measures the reproductive number often remains close to or above 1, highlighting the potential for propagating epidemics (Garske et al 2007).…”
Section: Discussioncontrasting
confidence: 85%
“…Hence, it was striking that free-range poultry had the lowest viral prevalence and diversity, likely reflecting their low population density and relative isolation compared with economic flocks (Stegeman et al, 2004). However, free-range poultry may still play an important role in AIV ecology and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that within each treatment all susceptible birds are equally susceptible, all infectious birds are equally infectious, and that each infectious bird is equally infectious over time. Furthermore, it is assumed that each infected bird constitutes an independent risk to infect a susceptible bird.ˇfollows from the intercept of the model, and subsequently the reproduction ratio R 0 can be estimated by taking the product of the estimatedˇand the estimated mean length of the infectious period, with the latter directly observed from the unvaccinated contact turkeys [17,18]. Virus shedding was compared between inoculated unvaccinated and vaccinated birds by means of a Fisher's exact test, and the NPAR1WAY procedure in SAS ® was used to compare HI antibody titres between groups.…”
Section: Discussionmentioning
confidence: 99%